2018
DOI: 10.1021/acsnano.7b07732
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Resolution Imaging of Nanoscale Chemical Expansion in PrxCe1–xO2−δ during In Situ Heating

Abstract: Thin film nonstoichiometric oxides enable many high-temperature applications including solid oxide fuel cells, actuators, and catalysis. Large concentrations of point defects (particularly, oxygen vacancies) enable fast ionic conductivity or gas exchange kinetics in these materials but also manifest as coupling between lattice volume and chemical composition. This chemical expansion may be either detrimental or useful, especially in thin film devices that may exhibit enhanced performance through strain enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 65 publications
(143 reference statements)
1
18
0
Order By: Relevance
“…171 This was explained by the chemical expansion due to the defect formation relieving the stress, 172 and is closely related to the anisotropic – in directions parallel and normal to the interface – chemical strain observed with in situ TEM, scanning transmission electron microscopy (STEM), electron energy loss spectroscopy (EELS) and optical strain measurements in Ce 1– x Pr x O 2– δ thin films on a YSZ substrate. 172,173 The anisotropic character of chemical expansion was also found in perovskite-based epitaxial thin films using XRD. 174 Both experimental and computational studies 175,176 showed that the nature of the substrate determines the presence of compressive or tensile in-plane strain in perovskite La 1– x Sr x CoO 3− δ films, which impacts the oxygen vacancy concentration therein, influencing such properties as the oxygen evolution reaction (OER) activity, 175 oxygen surface exchange and diffusion.…”
Section: Atomistic Insightsmentioning
confidence: 93%
“…171 This was explained by the chemical expansion due to the defect formation relieving the stress, 172 and is closely related to the anisotropic – in directions parallel and normal to the interface – chemical strain observed with in situ TEM, scanning transmission electron microscopy (STEM), electron energy loss spectroscopy (EELS) and optical strain measurements in Ce 1– x Pr x O 2– δ thin films on a YSZ substrate. 172,173 The anisotropic character of chemical expansion was also found in perovskite-based epitaxial thin films using XRD. 174 Both experimental and computational studies 175,176 showed that the nature of the substrate determines the presence of compressive or tensile in-plane strain in perovskite La 1– x Sr x CoO 3− δ films, which impacts the oxygen vacancy concentration therein, influencing such properties as the oxygen evolution reaction (OER) activity, 175 oxygen surface exchange and diffusion.…”
Section: Atomistic Insightsmentioning
confidence: 93%
“…This leads to an overestimation of the expansivity, since the βC ≈ 3αC holds only in cases of isotropic expansion. The films can, however, be partially or fully compensated for in the out of plane expansion, [13] Figure 6b.…”
Section: Quantification Of the Contribution Of Chemical Expansion To The Raman Shiftmentioning
confidence: 99%
“…This requires control over the thin film structure-property relationships such as fast reaction kinetics, ionic and electronic conductivities, [1,9] stoichiometry, [10] optical transmittance [11] and/or mechanical properties. [12,13] The small sample volumes, large interfacial areas and substrate confinement of the thin films often result in substantially altered properties when compared to macroscopic bulk Sr(Ti,Fe)O3-y specimens, processed by powder pressing and sintering at higher temperatures. [14,15] For example, when processed as a thin film, Sr(Ti,Fe)O3-y reveals a higher optical transmittance [11] and lower conductivity, [9] e.g.…”
Section: Introductionmentioning
confidence: 99%
“…© 2014, The Royal Society of Chemistry. (d) In situ phase contrast TEM images of PrxCe1-xO2-YSZ interface at 300°C and 650°C (upper panels) and temperature evolution of interfacial fringe width, W and periodicity, 𝜆 (lower panel) [20]. © 2018, American Chemical Society.…”
Section: Laboratory Based Techniquesmentioning
confidence: 99%
“…A beautiful example of the use of in situ TEM combined with scanning transmission electron microscopy (STEM) and electron energy loss spectroscopy (EELS) was reported for the study PrxCe1−xO2−δ (PCO) deposited as a thin film on YSZ [20]. By performing a series of consecutive experiments at three different temperatures (room temperature, 300 °C and 650°C) in oxidizing and reducing conditions, the authors were able to characterize chemical strains and changes in oxidation state in PCO lamella cross sections.…”
Section: Laboratory Based Techniquesmentioning
confidence: 99%